2011
DOI: 10.1007/s11708-011-0138-x
|View full text |Cite
|
Sign up to set email alerts
|

Combustion and emission characteristics of a turbo-charged common rail diesel engine fuelled with diesel-biodiesel-DEE blends

Abstract: The combustion and emission characteristics of a turbo-charged, common rail diesel engine fuelled with diesel-biodiesel-DEE blends were investigated. The study reports that the brake-specific fuel consumption of dieselbiodiesel-DEE blends increases with increase of oxygenated fuel fractions in the blends. Brake thermal efficiency shows little variation when operating on different dieselbiodiesel-DEE blends. At a low load, the NO x emission of the diesel-biodiesel-DEE blends exhibits little variation in compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Nabi et al[1] also reported lower PN emissions with oxygenated fuels. The current investigation is in good agreement with those in references[1,36,39,40].…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Nabi et al[1] also reported lower PN emissions with oxygenated fuels. The current investigation is in good agreement with those in references[1,36,39,40].…”
supporting
confidence: 92%
“…Figures 9(a-c) represent the particle number (PN) size distributions for three different speeds at 25% of full It is interesting to note that all oxygenated blends consistently reduce PN emissions for all three speeds. It is reported that the PN reduction is due to the presence of fuel-borne oxygen, less aromatic and sulphur in the oxygenated blends[39]. Liang et al did an experiment with oxygen enrichment and water-diesel emulsion to investigate the effect of oxygen enriched combustion[40] and reported lower PN emissions with oxygen enrichment at accumulation mode.…”
mentioning
confidence: 99%
“…Similar to PM emissions, at all loads PN emissions were also reduced for essential oil blends. Addition of oxygen and reduced carbon content in the blends could result in primary particles oxidation and thus reduce particle number emissions. , Compared to neat diesel, for eucalyptus and tea tree oil blends the PN emission reduced by 20–39% and 7–31%, respectively.…”
Section: Resultsmentioning
confidence: 91%
“…Addition of oxygen and reduced carbon content in the blends could result in primary particles oxidation and thus reduce particle number emissions. 35,36 Compared to neat diesel, for eucalyptus and tea tree oil blends the PN emission reduced by 20−39% and 7−31%, respectively. Figure 11 represents the distribution of particle size of the tested blends.…”
Section: Resultsmentioning
confidence: 99%
“…22 By rising CIT, the rate of cylinder pressure becomes higher during the initial stage of combustion and the peak pressure occurs slightly past. 39 By the growing of EGR rate, the cylinder pressure decreases due to the long ignition delay and moving the combustion process toward the expansion stroke. 19 The increased EGR rate leads to delay in ignition, therefore the main burning phase moves toward the power stroke.…”
Section: Resultsmentioning
confidence: 99%